# Math destroyer test twelve question twenty eight

Vendor
15+ Year Member

#### 510586

5+ Year Member
Oh shoot I'm a fool I thought it was (1+a)/(1-a) for some reason. Thanks!

• orgoman22

#### 510586

5+ Year Member
PHAT FINGER HA! #### byahnoob

5+ Year Member     #### neoking77

10+ Year Member
It should technically be

f(1-x) = (1-x) + 2
which simplifies to
f(1-x) = 1-x+2
f(1-x) = 3-x

So the bootcamp answer just took a shortcut and didn't bother putting in the paranthesis. The end result is the same.

Last edited:

#### 510586

5+ Year Member
It should technically be

f(1-x) = (1-x) + 2
which simplifies to
f(1-x) = 1-x+2
f(1-x) = 3-x

So the bootcamp answer just took a shortcut and didn't bother putting in the paranthesis. The end result is the same.
Why is it not 1-(x+2)? If fx=x+2 shouldn't f(-x)=-(x+2)?

#### neoking77

10+ Year Member
Why is it not 1-(x+2)? If fx=x+2 shouldn't f(-x)=-(x+2)?

We're given f(x-1) = x+1
then f(x) = x+2
Remember f(x) means you're replacing whatever's in f(x) into the x value. Try putting the first one back into the equation
f(x-1) = (x-1) +2 = x-1 +2 = x+1

f(-x) = (-x) +2 = -x+2

f(1-x)= (1-x) + 2 = 1-x+2 = 3-x

• 510586

#### orgoman22

##### DAT DESTROYER
Vendor
15+ Year Member
(x-1)=x+1. f(x-1+1)=x+2. Then f(x)=x+2.
To find f(1-x) we will first find f(-x) then add 1. f(-x)= -x+2 then f(-x+1)=f(1-x) = -x+2+1 = 3-x

• 510586

#### 510586

5+ Year Member
(x-1)=x+1. f(x-1+1)=x+2. Then f(x)=x+2.
To find f(1-x) we will first find f(-x) then add 1. f(-x)= -x+2 then f(-x+1)=f(1-x) = -x+2+1 = 3-x
Oh yea negative sign only affects the x right? Think that's what I was confused on

#### 510586

5+ Year Member
We're given f(x-1) = x+1
then f(x) = x+2
Remember f(x) means you're replacing whatever's in f(x) into the x value. Try putting the first one back into the equation
f(x-1) = (x-1) +2 = x-1 +2 = x+1

f(-x) = (-x) +2 = -x+2

f(1-x)= (1-x) + 2 = 1-x+2 = 3-x
Thank-you